Freedom of environmental information : aspirations and practice - Whittaker, Sean; Reid, Colin T.; Mendel, Jonathan (Cambridge, United Kingdom : Intersentia, 2023)
"This book explores the right of access to environmental information, considering both the environmental aspirations which underlie the right and how far these are evidenced in the right's use in practice. The right has a history separate from wider moves towards freedom of information. From its origins in the Rio Declaration to its current embodiment in the Aarhus Convention, a key aim of the right is to promote environmental governance and protect the environment through the provision of environmental information, both proactively and upon request. However, there is little empirical evidence to show whether the right is achieving these environmental aims, if it is being used for its intended environmental purpose, or even how far it is being viewed as distinct from the general right to information. This book seeks to fill this gap through qualitative research conducted in Scotland, the findings of which highlight that individuals who seek environmental information under the right are often doing so for personal or professional reasons that do not further the right's environmental purpose. This is significant, because if the right is not being used for its intended environmental purpose, then its contribution to environmental governance can be questioned, as can the value of maintaining this specific right, distinct from wider freedom of information laws."--
Introduction -- Theoretical and legal frameworks -- Professional users -- Personal users -- Information and participation -- Non-human actors -- Reflections and lessons.
BIBINDX
Keywords: Environmental law, International; Freedom of information (International law)